Engineering a minimal cloning vector from a pUC18 plasmid backbone with an extended multiple cloning site - Jens Staal; Kübra Alci; Wouter De Schamphelaire; Martine Vanhoucke; Rudi Beyaert (BioTechniques, 2019)
Minimal plasmids play an essential role in many intermediate steps in molecular biology. For example, they can be used to assemble building blocks in synthetic biology or be used as intermediate cloning plasmids that are ideal for PCR-based mutagenesis methods. A small backbone also opens up for additional unique restriction enzyme cloning sites. Here we describe the generation of pICOz, a 1185-bp fully functional high-copy cloning plasmid with an extended multiple cloning site. We believe that this is the smallest high-copy cloning vector ever described.